PENGARUH APLIKASI BERBAGAI PUPUK ORGANIK DAN PUPUK TSP TERHADAP PERTUMBUHAN SERTA PRODUKSI TANAMAN JAWAWUT (Seteria italica) - Gunawan Santoso; Siti Zahrah; Sri Mulyani (UIR Press, 2025)
The purpose of this study was to determine the effect of interaction and the main influence of various organic fertilizers and TSP fertilizers on the growth and yield of millet. The design used was a completely randomized factorial design consisting of two factors. The first factor was various organic fertilizers (T) with 4 levels: quail manure, goat manure, and TASPU fertilizer; the second factor was TSP fertilizer (P) with 4 levels: 0, 14, 22, and 28 grams per plot. The parameters observed were plant height, flowering age, number of productive tillers, harvest age, panicle length, production per clump, production per plot, and harvest index. The observation data were analyzed statistically and followed by a further test of Honestly Significant Difference (HSD) at the 5% level. The results showed that the interaction of various organic fertilizers and TSP fertilizers affected all observation parameters, namely plant height, flowering age, number of productive tillers, harvest age, panicle length, production per clump, production per plot, and harvest index. The best treatment of quail manure fertilizer was 2.1 kg/plot and TSP 20 grams/plot (K1P3). The main effect of quail manure fertilizer was observed across all observation parameters. The best treatment was the application of 2.1 kg/plot (K1). The main impact of TSP fertilizer application was observed across all observation parameters, namely plant height, flowering age, number of productive tillers, harvest age, panicle length, production per clump, production per plot, and harvest index, with the best treatment being 28 g/plot.